Clustering of cardiovascular risk factors in semi-urban communities in south-western Nigeria - Oluyombo, R (Cardiovasc J Afr, 2016)
BACKGROUND: In addition to poor socio-economic indices and a high prevalence of infectious diseases, there have been various reports of a rising prevalence of cardiovascular diseases, with associated morbidity and mortality in developing countries. These factors co-exist, resulting in a synergy, with serious complications, difficult-to-treat conditions and fatal outcomes. Hence this study was conducted to determine the clustering of cardiovascular disease risk factors and its pattern in semi-urban communities in south-western Nigeria. METHODS: This was a cross sectional study over seven months in 11 semi-urban communities in south-western Nigeria. RESULTS: The total number of participants was 1 285 but only 1 083, with 785 (65%) females, completed the data. Participants were 18 years and older, and 51.2% were over 60 years. The mean age was 55.12 ± 19.85 years. There were 2.6% current cigarette smokers, 22% drank alcohol and 12.2% added salt at the table, while 2% had been told by their doctors they had diabetes, and 23.6% had hypertension. The atherogenic index of plasma was at a high-risk level of 11.1%. Elevated total cholesterol and low-density lipoprotein cholesterol, and low high-density lipoprotein cholesterol levels were seen in 5.7, 3.7 and 65.1%, respectively. Prevalence of hypertension was 44.9%, diabetes was 5.2%, obesity with body mass index (BMI) > 30 kg/m(2) was 5.7%, and abdominal circumference was 25.7%. Prevalence of clusters of two, three, and four or more risk factors was 23.1, 15.5 and 8.4%, respectively. Increasing age 2.94 (95% CI: 1.30–6.67), BMI 1.18 (95% CI: 1.02–1.37), fasting plasma glucose level 1.03 (95% CI: 1.00– 1.05), albuminuria 1.03 (95% CI: 1.00–1.05), systolic blood pressure 1.07 (95% CI: 1.04–1.10), diastolic blood pressure 1.06 (95% CI: 1.00–1.11) and female gender 2.94 (95% CI: 1.30–6.67) showed increased odds of clustering of two or more cardiovascular risk factors. CONCLUSION: Clustering of cardiovascular risk factors is prevalent in these communities. Patterns of clustering vary. This calls for aggressive and targeted public health interventions to prevent or reduce the burden of cardiovascular disease, as the consequences could be detrimental to the country.